Roles of Heritage Resources in Tourism Development: Expose on Patronage and Management Practices in Nike Art Gallery, Osogbo, Osun State, Nigeria - Olubukola Mary Ogundare; Emmanuel Thomas; Omolola Oluwakemi Ajayi; Mutiu Kolawole Ambali (Journal of Tourismology)
Nike Art Gallery is a legacy handcraft that comprises numerous displays of art and culture developed with the intention of establishing and nurturing an atmosphere conducive to the growth of art in Africa. Despite its presence for approximately 30 years, a paucity in empirical research has occurred on its activities. To address this concern, this study evaluates the patronage patterns and management strategies implemented by Nike Art Gallery in other to know the contribution of the gallery to tourism development. A semi-structured interview was conducted with the two directors of the Gallery with secondary data on influx and revenue. The result revealed that the Gallery receives many visitors for educational, recreational, and other purposes. Students on group excursions paid nominal fees ranging from N300 to N500 per group with average weekly and monthly earnings for the Gallery reaching N10250 and N30000, respectively. The administration of the Gallery is focused on tourism promotion, sales and marketing, and staff training. Nike Art Gallery was found to be a significant heritage treasure that promotes people empowerment and growth but with little tourism impact. Thus, efforts should be exerted to improve its tourism value and, consequently, its socioeconomic contribution to the community.